Inovasi Pertanian: Meningkatkan Ekonomi dengan Tanaman Hidroponik - Rizma Melina Oktabian Alifani; Ernawati Ernawati; She Fira Azka Arifin; Siti Kholidatur Rodiyah; Mirza Elmy Safira; Rahayu Mardikaningsih; Yayu Sriwahyuni Hamzah (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
Hydroponic plants are plants that grow using hydro or water media. This plant is more efficient in saving space, soil media and fertilizer and so on. This community service research aims to describe strategies for improving the economy of PKK mothers by implementing the idea of hydroponic plants in Pertanmaduretno Village, Taman District, Sidoarjo Regency. The author used descriptive qualitative research with observation and documentation data collection techniques at the research location. Data analysis techniques use data collection, data presentation, data condensation, and data conclusion. The results of the research show that the hydroponic plant strategy is effective in improving the economy of PKK mothers. The author participated in observing and playing a direct role in planting hydroponic plants.